Agile Leadership in Digital Work Systems: Psychological Pathways to Innovation and Employee Performance - Tiong, Piter; Adi, Yusram; Nuryadin, Andi; Soemaryo, Partono; Irwan, Andi (Jurnal Aplikasi Manajemen, 2026)
Organizations increasingly rely on adaptive leadership practices and digital human resource management systems to sustain innovation and employee performance in rapidly changing work environments. However, limited research has examined how these organizational factors jointly influence employees’ psychological resources and behavioral outcomes. Drawing on social cognitive and socio-technical perspectives, this study investigates how leadership agility and digital human resource management influence self-efficacy, innovative work behavior, and work performance, while also examining psychological safety as a contextual boundary condition. A quantitative explanatory design was employed using survey data collected from 392 employees working in education, service, and digital-based organizations. The proposed model was tested using partial least squares structural equation modeling. The findings indicate that leadership agility and digital HRM significantly enhance employees’ self-efficacy and innovative work behavior. Self-efficacy positively influences both innovative behavior and work performance, while innovative work behavior emerges as the strongest predictor of employee performance. Mediation analysis further reveals that self-efficacy and innovative behavior serve as key psychological and behavioral mechanisms linking leadership and HR practices to performance outcomes. In addition, psychological safety strengthens the influence of leadership agility on innovative work behavior, suggesting that agile leadership becomes more effective in supportive interpersonal climates. The study contributes to leadership and digital HRM literature by integrating adaptive leadership, digital HR practices, and employee psychological mechanisms within a unified framework. For managers, the findings highlight that investing in agile leadership development, implementing digital HR platforms that support continuous learning and feedback, and fostering psychologically safe team environments can significantly enhance employee innovation and performance.